2010
DOI: 10.1309/ajcp0f6axrcjmqqg
|View full text |Cite
|
Sign up to set email alerts
|

Automated Heart-Type Fatty Acid–Binding Protein Assay for the Early Diagnosis of Acute Myocardial Infarction

Abstract: We compared an automated quantitative heart-type fatty acid-binding protein (H-FABP) assay with other cardiac-marker assays to examine its usefulness as an early diagnostic marker of acute myocardial infarction (AMI). Serum samples for cardiac troponin T (cTnT), creatine kinase-MB isozyme (CK-MB), myoglobin, and H-FABP were obtained from 64 patients with AMI and 53 patients with other conditions (control group). H-FABP was measured by using 2 immunoassays, the H-FABP enzyme-linked immunosorbent assay (ELISA; B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…Serum troponin-I [8] and myoglobin [9] levels were measured by chemiluminescence immunoassay on Abbott Architect c4000 analyser (Abbott Laboratories, Illinois, USA) and serum CK-MB by Immuno-inhibition method [10,11] using Stat Fax 3300 Biochemistry analyser (Awareness Technology Inc., Florida, USA). Serum H-FABP levels were measured by Automated Immunoturbidimetric method [12,13] (Reagent kit from Randox Laboratories, and using Roche C-311 fully automated Biochemistry analyser). The method is based on the principle that, H-FABP present in the sample reacts with buffer and anti-H-FABP coated latex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum troponin-I [8] and myoglobin [9] levels were measured by chemiluminescence immunoassay on Abbott Architect c4000 analyser (Abbott Laboratories, Illinois, USA) and serum CK-MB by Immuno-inhibition method [10,11] using Stat Fax 3300 Biochemistry analyser (Awareness Technology Inc., Florida, USA). Serum H-FABP levels were measured by Automated Immunoturbidimetric method [12,13] (Reagent kit from Randox Laboratories, and using Roche C-311 fully automated Biochemistry analyser). The method is based on the principle that, H-FABP present in the sample reacts with buffer and anti-H-FABP coated latex.…”
Section: Methodsmentioning
confidence: 99%
“…The cut off levels and coefficients of variation (CV) of H-FABP, troponin-I, myoglobin and CK-MB used for the diagnosis of AMI in this study were >6.32ng/ml (at 99 th percentile & CV = 7.94%), >0.032 µg/L in males & >0.022 µg/L in females (at 99 th percentile & CV = 10%), >106 ng/ml in males & >155 ng/ml in females (at 99 th percentile & CV = 7.94%) and 24 IU/L respectively. These values are according to the recommendations of the reagent kit manufacturers [8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…It is rapidly released into the circulation after the onset of myocardial injury owing to its low molecular weight and cytoplasmic localisation 27. Agnello et al 28 found that early diagnosis of AMI was possibly based on measurement of hFABP level.…”
Section: Summary Of Cardiac Biomarkersmentioning
confidence: 99%
“…19 This difference might be due to differences not only in URL level, but also in the characteristics of study subjects. Their study also revealed that cTnT and CK-MB showed low sensitivity in patients admitted within 6 hours after onset of chest pain and high sensitivity in patients admitted 6 to 8 hours after onset of symptoms, and there was a significant difference in sensitivity between the 2 patient groups.…”
Section: Discussionmentioning
confidence: 99%